Model Pengembangan Sistem Manajemen Pesanan Halal (OMS) untuk Bisnis Online Pet Shop di Indonesia - Ricky Aditya; Effy Zalfiana Rusfian (Society, 2024)
The rapid growth of the pet shop industry in Indonesia highlights the need for an efficient and halal-compliant operational system to meet the increasing demand for halal-certified products among Muslim consumers. This study proposes the development and implementation of a Halal Online Management System (OMS) that integrates real-time inventory management, order processing, shipment tracking, and compliance with halal standards. Using Soft Systems Methodology (SSM), the research addresses operational challenges, including stock errors, delivery inefficiencies, and the segregation of halal and non-halal products. The proposed system ensures a streamlined workflow while fostering transparency and trust among stakeholders. The implications of this system are significant for stakeholders: consumers benefit from assured halal compliance and enhanced service quality, employees experience greater efficiency through automated processes, and business owners gain a competitive advantage in a rapidly evolving market. Additionally, logistics providers benefit from improved shipment accuracy and operational collaboration. By aligning business practices with halal principles, the system not only boosts customer satisfaction but also reinforces ethical and religious values in the supply chain. This conceptual model has broader implications for advancing halal business practices and offers a scalable framework for similar industries. Further research is recommended to empirically validate the system’s impact on stakeholder engagement and business performance.